Molecular mechanism of the tree shrew’s insensitivity to spiciness - Han, Yalan; Li, Bowen; Yin, Ting-Ting; Xu, Cheng; Ombati, Rose; Luo, Lei; Xia, Yujie; Xu, Lizhen; Zheng, Jie; Zhang, Yaping; Yang, Fan; Wang, Guo-Dong; et al. (PLOS Biology, 2018)
Author summary Most mammals cannot tolerate the pungent sensation, such as that evoked by eating chili peppers. Here, we show that unexpectedly, the tree shrew, a mammal closely related to primates, can consume pungent plants. We determined that this tolerance is caused by an amino acid change in the tree shrew’s transient receptor potential vanilloid type-1 (TRPV1) ion channel, which lowers the channel’s sensitivity to capsaicinoids—the substances that make plants spicy. We attribute the strong selection for this amino acid to an adaptation to consuming Piper boehmeriaefolium, a spicy plant that geographically overlaps with the tree shrew and produces Cap2, a substance similar to capsaicin, the pungent agent found in chili peppers. Our study suggests an evolutionary and molecular mechanism adopted by the tree shrew to expand its nutritional repertoire.